Application of Audio Visual Media to Improve Drama Text Writing Skills through Project Based Learning (PjBL) Model - Muryati, Muryati; Missriani, Missriani; Rukiyah, Siti (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to determine and describe the application of audio-visual media to improve the ability to write drama texts through the project-based learning (PjBL) model for class VIII students of SMP Negeri 5 Mesuji. This study is included in classroom action research (PTK) with 20 students as research subjects. The data collection method uses test, observation, interview, and documentation methods. The data analysis technique uses quantitative methods to observe student performance and assess the results of work in the form of drama texts. The results of the study indicate that the use of audio-visual media and the project-based learning model can improve the quality of learning to write drama texts, seen from changes in student attitudes in several aspects. Teacher activity in cycle I with a total score percentage obtained of 71.67% increased to 90% in cycle II. While student activity in cycle I with a total score percentage obtained of 70% and increased in cycle II to 86.7%. The total value of students' drama text writing skills in cycle I obtained 1035 or the average value of students classically was 51.75 with a percentage of completion of 10%. In cycle II, the total value of drama text writing skills increased by 1645 or the average value classically was 82.25 with a percentage of completion reaching 80%.